Observation on gonad maturation of the first generation (F1) of humpback grouper, Cromileptes altivelis - Tridjoko Tridjoko; Eri Setiadi; Suko Ismi; Fris Johnny (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2006)
The purpose of this experiment was to know gonad maturation and spawning frequency of the first generation in humpback grouper, Cromileptes altivelis. This experiment had two groups of feed types (A and B). Both groups were put in circular concrete tanks with water volume of 75 m3 each. Each tank was stocked 40 fishes with body weight of 500—1,000 g/fish and total length of 28—38 cm. Group (A) was fed with trash fish, squid, and vitamin mix, while group (B) was fed with artificial diet. Both groups were fed once a day, in the morning. The water was exchange continuously, of 300%—500% per day. The result showed the fish spawn after 31 months rearing. During the experiment, the range of water temperature and salinity were 28.4°C—31.7°C and 30.2—34.4 ppt, respectively.